2015
DOI: 10.1681/asn.2014121200
|View full text |Cite
|
Sign up to set email alerts
|

Defective Store-Operated Calcium Entry Causes Partial Nephrogenic Diabetes Insipidus

Abstract: Store-operated calcium entry (SOCE) is the mechanism by which extracellular signals elicit prolonged intracellular calcium elevation to drive changes in fundamental cellular processes. Here, we investigated the role of SOCE in the regulation of renal water reabsorption, using the inbred rat strain SHR-A3 as an animal model with disrupted SOCE. We found that SHR-A3, but not SHR-B2, have a novel truncating mutation in the gene encoding stromal interaction molecule 1 (STIM1), the endoplasmic reticulum calcium (Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 66 publications
(101 reference statements)
1
41
0
Order By: Relevance
“…Thus, Mamenko et al 2 identified a novel genetic mutation and a novel physiologic mechanism for NDI through SOCE and STIM1 and elucidated an important role for Ca 21 signaling in the urinary concentrating mechanism. 2 The paper in JASN by de Groot et al 3 addressed a different aspect of NDI: a new therapeutic approach to lithiuminduced NDI. Lithium is used to treat manic depressive illness (reviewed in ref.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, Mamenko et al 2 identified a novel genetic mutation and a novel physiologic mechanism for NDI through SOCE and STIM1 and elucidated an important role for Ca 21 signaling in the urinary concentrating mechanism. 2 The paper in JASN by de Groot et al 3 addressed a different aspect of NDI: a new therapeutic approach to lithiuminduced NDI. Lithium is used to treat manic depressive illness (reviewed in ref.…”
mentioning
confidence: 99%
“…Mamenko et al 2 used whole-genome sequencing to uncover this novel mutation in the STIM1 gene. Mamenko et al 2 made this discovery using a clever approach: they crossed SHR-A3 rats with a very closely related rat, the SHR-B2. The SHR-B2 rat shares 87% of its genome with the SHR-A3 rat but lacks the STIM1 mutation present in the SHR-A3 rat.…”
mentioning
confidence: 99%
See 3 more Smart Citations